Costly posturing: relative status, ceremonies and early child development in China - Chen, Xi; Zhang, Xiaobo (International Food Policy Research Institute, 2012)
Participating in and presenting gifts at funerals, weddings, and other ceremonies held by fellow villagers have been regarded as social norms in Chinese villages for thousands of years. However, it is more burdensome for the poor to take part in these social occasions than for the rich. Because the poor often lack the necessary resources, they are forced to cut back on basic consumption, such as food, in order to afford a gift to attend the social festivals. For pregnant women in poor families, such a reduction in nutrition intake as a result of gift-giving can have a lasting detrimental health impact on their children.